Next‐Generation Head‐Up Displays. Issue 3 (1st May 2015) - Rankin, Alan; Thompson, Jason
Abstract : HUD 2.0 may function as a primary information‐display technology for vehicle drivers rather than a source of merely helpful or ancillary information.